Strength Design on Permanent Magnet Rotor in High Speed Motor Using Finite Element Method - Tao Zhang; Xiaoting Ye; Huiping Zhang; Hongyun Jia (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The permanent magnets can be damaged for the tremendous centrifugal stress when the permanent magnet rotor rotates in high-speed. In this paper, the mechanical strength of high-speed permanent magnet rotor was researched. Stability operation mechanical conditions of the surface-mounted permanent magnet rotor were analyzed. The mathematical model between the shrink range of bandage and the maximum operating speed were concluded. The strengths of two kinds of surface-mounted permanent magnet rotors were calculated and compared using contact finite element method. For buried type permanent magnet rotor, the equivalent ring method was put forward to calculate its stress limit. The mathematical relationships between the maximum velocity and iron bridge thickness has been deduced. Using finite element method, the stress distributions was analyzed. The research results have shown that the high speed permanent magnet rotors designed according to the method proposed here had the adequate mechanical strength. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4675